2024
DOI: 10.3390/fire7020043
|View full text |Cite
|
Sign up to set email alerts
|

Ignition Delay and Reaction Time Measurements of Hydrogen–Air Mixtures at High Temperatures

Yauhen Baranyshyn,
Vyacheslav Kuzmitski,
Oleg Penyazkov
et al.

Abstract: Induction and reaction times of hydrogen–air mixtures (ϕ = 0.5–2) have been measured behind reflected shock waves at temperatures of 1000–1600 K, pressures of 0.1, 0.3, 0.6 MPa in the domain of the extended second explosion limit. The measurements were performed in the shock tube with a completely transparent test section of 0.5 m long, which provides pressure, ion current, OH and high-speed chemiluminescence observations. The experimental induction time plots demonstrate a clear increasing of the global activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The diameter of each nozzle is mm, and they are perpendicular to the wall surface. A1 and A2 are located on the uppe Hydrogen-fueled scramjet engines, due to their high specific impulse characteristics, have broad application prospects in hypersonic vehicles; hence, researchers have conducted numerous simulations of hydrogen fuel combustion [23][24][25][26][27][28][29][30]. Wang et al [23] conducted research on the combustion performance of a hydrogen-fueled scramjet engine, revealing a positive feedback relationship between the lift shear layer in the recirculation zone and enhanced combustion, which demonstrates the strong robustness of the shear layer/recirculation stable combination mode.…”
Section: Computational Domain and Relevant Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The diameter of each nozzle is mm, and they are perpendicular to the wall surface. A1 and A2 are located on the uppe Hydrogen-fueled scramjet engines, due to their high specific impulse characteristics, have broad application prospects in hypersonic vehicles; hence, researchers have conducted numerous simulations of hydrogen fuel combustion [23][24][25][26][27][28][29][30]. Wang et al [23] conducted research on the combustion performance of a hydrogen-fueled scramjet engine, revealing a positive feedback relationship between the lift shear layer in the recirculation zone and enhanced combustion, which demonstrates the strong robustness of the shear layer/recirculation stable combination mode.…”
Section: Computational Domain and Relevant Parametersmentioning
confidence: 99%
“…Takeno et al [24] conducted research on the flame stabilization mechanisms of hydrogen jets and found that spherical flame structures are instrumental in sustaining the flame. Baranyshyn et al [25] studied the ignition timing of hydrogen-air mixtures at elevated temperatures and found that with the increase in temperature, the delay before spontaneous ignition sharply decreases from hundreds of mi-Fire 2024, 7, 176 3 of 20 croseconds to just a few microseconds. Koo et al [26] studied the effect of thermodynamic nonequilibrium on the flame structure of supersonic hydrogen combustion using direct numerical simulation (DNS).…”
Section: Computational Domain and Relevant Parametersmentioning
confidence: 99%